Battery and electronic equipment

CN119678257APending Publication Date: 2025-03-21ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380014445.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

High-specific energy lithium-ion batteries have poor thermal stability in furnace temperature tests, resulting in voltage attenuation and high-temperature intermittent cycle failure, affecting the battery life.

Method used

A battery is designed, and its positive electrode sheet includes a positive electrode active material layer for thermogravimetric analysis under an oxygen atmosphere, with a weight loss rate of not more than 15% between 100°C and 600°C and obtained by polymerization of polymerized monomers. The electrolyte, which contains functional groups such as acrylate groups, combines lithium salts and non-aqueous organic solvents to form a stable electrolyte, which improves the thermal stability of the battery.

Benefits of technology

It effectively avoids voltage attenuation of the battery during furnace temperature test, reduces the risk of high-temperature intermittent cycle failure, improves the service life of the battery, and optimizes the energy density and cycling performance of the battery through appropriate porosity and density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119678257A_ABST
    Figure CN119678257A_ABST
Patent Text Reader

Abstract

A battery and an electronic device are provided. The battery comprises a positive pole piece, wherein the positive pole piece comprises a positive current collector and a positive active material layer arranged on the surface of the positive current collector; thermogravimetric analysis is carried out on the positive electrode active material layer at a heating rate of 5 DEG C / min in an oxygen atmosphere, and the positive electrode active material layer has at least one weightlessness peak between 100 DEG C and 600 DEG C. The problem of voltage attenuation of the battery in the furnace temperature testing process can be avoided, the risk of high-temperature intermittent cycle failure of the battery is reduced, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Battery and electronic device Technical Field

[0001] The present application belongs to the field of batteries and relates to a battery and an electronic device. Background Art

[0002] With the rapid development of new energy, lithium-ion batteries are in urgent need of high energy density and superior safety performance. Compared to traditional liquid batteries, high-energy-density batteries offer higher energy density and longer battery life, offering broader application prospects in new energy fields such as cutting-edge consumer electronics, electric vehicles, and energy storage devices. However, high-energy-density batteries suffer from poor thermal stability, experiencing voltage decay during furnace temperature testing, accelerating intermittent high-temperature cycling failure and shortening their service life.

[0003] Summary of the Invention

[0004] The present application provides a battery that can avoid the problem of voltage decay of the battery during furnace temperature testing, reduce the risk of high-temperature intermittent cycle failure of the battery, and increase the service life of the battery.

[0005] The present application also provides an electronic device comprising the battery.

[0006] In a first aspect, the present application provides a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on a surface of the positive electrode current collector;

[0007] In an oxygen atmosphere, a thermogravimetric analysis is performed on the positive electrode active material layer at a heating rate of 5° C. / min. The positive electrode active material layer has at least one weight loss peak between 100° C. and 600° C.

[0008] In the battery as described above, the weight loss rate of the positive electrode active material layer at 100° C. to 600° C. is not higher than 15%.

[0009] The battery as described above is subjected to thermogravimetric analysis of the positive electrode active material layer in an oxygen atmosphere, starting from an initial temperature T0 at a heating rate of 5°C / min, where the initial temperature T0 is 25°C;

[0010] The positive electrode sheet satisfies at least one of the following:

[0011] (1) When the temperature T reaches 100°C from T0, the weight loss rate of the positive electrode active material layer is 0.01% to 1.68%;

[0012] (2) When the temperature T increases from 100°C to 200°C, the weight loss rate of the positive electrode active material layer is 0.05% to 3.64%;

[0013] (3) When the temperature T increases from 200°C to 300°C, the weight loss rate of the positive electrode active material layer is 0.10% to 6.47%;

[0014] (4) When the temperature T increases from 300°C to 400°C, the weight loss rate of the positive electrode active material layer is 0.22% to 8.77%;

[0015] (5) When the temperature T increases from 400°C to 500°C, the weight loss rate of the positive electrode active material layer is 0.66% to 10.47%;

[0016] (6) When the temperature T increases from 500°C to 570°C, the weight loss rate of the positive electrode active material layer is 0.93% to 12.66%.

[0017] In the battery as described above, the porosity of the positive electrode sheet is 15% to 40%.

[0018] The battery as described above has a true density of 3.5 to 4.5 g / cm 3 .

[0019] The battery as described above has a compaction density of the positive electrode sheet of 2.8 to 4.5 g / cm 3 .

[0020] In the battery as described above, the positive electrode sheet includes an electrolyte.

[0021] In the battery as described above, the electrolyte includes a polymer obtained by polymerizing a monomer, the monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0022] The battery as described above is obtained by sequentially subjecting a battery precursor to a curing treatment, a curing treatment, and a formation treatment;

[0023] The curing treatment comprises: charging the battery precursor to a voltage of 3.7 V at a temperature of 60° C. to 80° C., a pressure of ≤5 MPa, and a rate of ≤0.3C;

[0024] The curing treatment comprises: curing the battery precursor after the curing treatment at a temperature of 60° C. to 90° C. and a pressure of ≤5 MPa for a time of 2 hours to 8 hours;

[0025] The formation treatment comprises: charging the cured battery precursor to a cut-off voltage of ≥4.0V at a temperature of 60°C to 80°C, a pressure of ≤5MPa, and a rate of ≤0.5C.

[0026] The battery as described above includes an electrolyte, wherein the electrolyte includes a polymer obtained by polymerizing a polymerized monomer, wherein the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0027] In the battery as described above, the polymerizable monomer is selected from one or more of a bifunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer;

[0028] The bifunctional monomer is selected from one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, ethoxylated bisphenol A diacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, neopentyl glycol diacrylate and its derivatives, and 1,5-pentanediol diacrylate and its derivatives;

[0029] And / or, the trifunctional monomer is selected from one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives, and pentaerythritol triacrylate and its derivatives;

[0030] and / or, the tetrafunctional monomer is ethoxylated (5) pentaerythritol tetraacrylate and its derivatives;

[0031] And / or, the hexafunctional monomer is dipentaerythritol hexaacrylate and its derivatives.

[0032] In the battery as described above, the electrolyte further comprises a lithium salt and a non-aqueous organic solvent.

[0033] The battery as described above, wherein the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide;

[0034] And / or, the non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

[0035] In the battery as described above, the electrolyte includes an additive, and the additive includes one or more of tris(trimethylsilyl)borate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate), tetramethyl borate, trimethyl borate, trimethylcyclotriboroxane, tris(2,2,2-trifluoroethyl)phosphite, triphenylphosphite, tris(trimethylsilyl)phosphite, trimethyl phosphite, triallyl phosphate, 1,3-propane sultone, trifluoromethylphenyl sulfide, allyloxytrimethylsilyl, 1,3,5-hydroxybenzene, cyclohexylbenzene, ethylene sulfite, ethylene sulfate, propylene sulfite, ethylene carbonate, ethylene ethylene carbonate, propylene sulfate, phenylacetone, 1,4-butane sultone, 1,3-propane sultone, 4-methylethylene sulfate, 4-methylethylene sulfite, diethyl(cyanomethyl)phosphate, N,N-dimethylamide, and methylene methanedisulfonate.

[0036] In the battery as described above, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.

[0037] The battery as described above is a solid-state battery or a semi-solid-state battery.

[0038] In the battery as described above, the electrolyte is a semi-solid electrolyte or a solid electrolyte.

[0039] The battery as described above also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of silicon, silicon carbon, SiOx, lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, and copper nitride.

[0040] A second aspect of the present application provides an electronic device comprising any of the above-mentioned batteries.

[0041] The battery provided in this application can avoid the problem of voltage decay of the battery during furnace temperature testing, reduce the risk of high-temperature intermittent cycle failure of the battery, and increase the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] FIG1 is a schematic structural diagram of the positive electrode sheet provided in this application;

[0043] FIG2 is a thermogravimetric curve of the positive electrode active material layer provided in Example 1 of the present application;

[0044] FIG3 is a thermogravimetric curve of the positive electrode active material layer provided in Example 2 of the present application;

[0045] FIG4 is a thermogravimetric curve of the positive electrode active material layer provided in Example 3 of the present application;

[0046] FIG5 is a thermogravimetric curve of the positive electrode active material layer provided in Example 4 of the present application.

[0047] Explanation of reference numerals: 1-positive electrode current collector; 2-positive electrode active material layer. DETAILED DESCRIPTION

[0048] To make the purpose, technical solutions, and advantages of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0049] Figure 1 is a schematic structural diagram of the positive electrode plate provided in the present application. As shown in Figure 1, the positive electrode plate includes a positive electrode collector 1 and a positive electrode active material layer 2 arranged on the upper surface and the lower surface of the positive electrode collector; it can be understood that the positive electrode active material layer 2 can also be arranged on the upper surface or the lower surface of the positive electrode collector 1, and can be arranged according to actual needs.

[0050] The positive electrode sheet provided in the present application is subjected to thermogravimetric analysis of the positive electrode active material layer at a heating rate of 5°C / min in an oxygen atmosphere. The positive electrode active material layer has at least one weight loss peak between 100°C and 600°C.

[0051] During the test, the battery was first disassembled, the positive electrode sheet was taken and vacuumed at 25°C for 36 hours, and then the positive electrode active material layer was subjected to thermogravimetric analysis. The thermogravimetric analysis was performed in an oxygen atmosphere. The mass M0 of the positive electrode active material layer was tested at an initial temperature of 25°C, and then the temperature was increased at a rate of 5°C / min. The mass M of the positive electrode active material layer was tested at different temperature nodes. n , with temperature as the horizontal axis and the mass of the positive electrode active material layer as the vertical axis, a thermogravimetric analysis curve is obtained.

[0052] Furthermore, the weight loss rate of the positive electrode active material layer at 100° C. to 600° C. is not higher than 15%.

[0053] Furthermore, a thermogravimetric analysis of the positive electrode active material layer is performed under an oxygen atmosphere, starting from an initial temperature T0 at a heating rate of 5°C / min, wherein the initial temperature T0 is 25°C;

[0054] The positive electrode sheet satisfies at least one of the following:

[0055] (1) When the temperature T reaches 100°C from T0, the weight loss rate of the positive electrode active material layer is 0.01% to 1.68%;

[0056] (2) When the temperature T increases from 100°C to 200°C, the weight loss rate of the positive electrode active material layer is 0.05% to 3.64%;

[0057] (3) When the temperature T increases from 200°C to 300°C, the weight loss rate of the positive electrode active material layer is 0.10% to 6.47%;

[0058] (4) When the temperature T increases from 300°C to 400°C, the weight loss rate of the positive electrode active material layer is 0.22% to 8.77%;

[0059] (5) When the temperature T increases from 400°C to 500°C, the weight loss rate of the positive electrode active material layer is 0.66% to 10.47%;

[0060] (6) When the temperature T increases from 500°C to 570°C, the weight loss rate of the positive electrode active material layer is 0.93% to 12.66%.

[0061] As the test temperature continues to increase, the weight loss rate of the positive electrode active material layer provided by the present application is controlled within a certain range. On the one hand, the quality of its residual material is high and the heat loss is low, which helps to ensure the thermal stability of the positive electrode plate; on the other hand, when the temperature is increased to above 400°C, the weight loss rate of the positive electrode active material layer is controlled at above 0.6%, indicating that there are thermally decomposable substances in the positive electrode active material layer provided by the present application. These substances can absorb heat during the heating process, reduce the impact of temperature on the thermal stability and structural stability of the positive electrode plate, prevent the battery from voltage decay during the furnace temperature test, improve the high-temperature intermittent cycle performance of the battery, and increase the service life of the battery.

[0062] The weight loss rate can be understood as the percentage of the difference between the mass of the positive electrode active material layer at the initial temperature and the mass of the positive electrode active material layer at the end of the heating process to the mass of the positive electrode active material layer at the initial temperature. For example, when the temperature T reaches 100°C from T0, the weight loss rate of the positive electrode active material layer is 0.01% to 1.68%; that is, at T0, the mass of the positive electrode active material is M1, and the mass when it reaches 100°C is M2. The weight loss rate is (M1-M2) / M1*100%, and the value range of (M1-M2) / M1*100% is 0.01% to 1.68%.

[0063] In one embodiment, the porosity of the positive electrode sheet is 15% to 40%. When the porosity is too low, the degree of compression between the positive electrode active materials is greater, which affects the transmission rate of lithium ions and the electrochemical performance of the battery. When the porosity is too high, it indicates that the contact between the positive electrode active material particles is not tight, the transmission path of lithium ions and electrons is long, and the resistance is high. The appropriate porosity helps improve the overall performance of the battery. The porosity of the positive electrode sheet can be measured using conventional technical means in the field.

[0064] In a specific embodiment, the true density of the positive electrode sheet is 3.5 to 4.5 g / cm 3 The proper electrode true density determines the energy density of the battery. Therefore, the true density of the positive electrode provided in this application is controlled at 3.5 to 4.5 g / cm 3 , which helps to improve the energy density of the battery.

[0065] In a specific embodiment, the compaction density of the positive electrode sheet is 2.8 to 4.5 g / cm 3 Generally speaking, the compaction density is closely related to the electrode specific capacity, efficiency, internal resistance, and battery cycle performance. The greater the electrode compaction density, the more positive electrode active material the electrode can accommodate per unit volume, and the higher the battery capacity. However, too high a compaction density will seriously reduce the battery specific capacity and cycle performance. Therefore, appropriate compaction density helps to improve the battery capacity and cycle performance.

[0066] In a specific embodiment, the present application provides a positive electrode plate including an electrolyte. The electrolyte in the positive electrode plate can be added during the preparation of the positive electrode plate. For example, after preparing the positive electrode active material layer, the electrolyte is coated on the surface of the positive electrode active material layer, or the electrolyte and the positive electrode active material are blended to prepare a positive electrode active material layer slurry and coated on the surface of the positive electrode current collector; the electrolyte can also be added to the electrolyte precursor solution, and the electrolyte enters the positive electrode plate during the battery formation process.

[0067] Furthermore, the positive electrode plate provided in the present application is formed by adding an electrolyte into an electrolyte precursor solution, and then entering the positive electrode plate after treatment, to form the electrolyte. Specifically,

[0068] The electrolyte provided in the present application includes a polymerized monomer, wherein the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

[0069] Furthermore, the polymerizable monomer is selected from one or more of a difunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer.

[0070] Furthermore, a difunctional monomer refers to a polymer monomer containing two carbon-carbon double bonds, including but not limited to one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, ethoxylated bisphenol A diacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, neopentyl glycol diacrylate and its derivatives, and 1,5-pentanediol diacrylate and its derivatives.

[0071] A trifunctional monomer refers to a polymer monomer containing three carbon-carbon double bonds, including but not limited to one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives, and pentaerythritol triacrylate and its derivatives.

[0072] The tetrafunctional monomer refers to a polymer monomer containing four carbon-carbon double bonds, including but not limited to ethoxylated pentaerythritol tetraacrylate and its derivatives; the hexafunctional monomer includes but not limited to dipentaerythritol hexaacrylate and its derivatives.

[0073] It should be noted that the above-mentioned derivatives refer to products obtained by replacing the original groups in the main body with new substituent groups. For example, the derivatives of ethoxylated trimethylolpropane triacrylate refer to products obtained by replacing the original groups (e.g., hydrogen atoms) in ethoxylated trimethylolpropane triacrylate with substituent groups. The present invention is not limited to the specific choice of substituent groups, and for example, the substituent groups can be at least one of halogen atoms, hydroxyl groups, thiol groups, nitro groups, cyano groups, isocyano groups, sulfone groups, hydroxylamine groups, carboxyl groups, carbonyl groups, aromatic hydrocarbons, heteroaromatic hydrocarbons, heterocycloalkyl groups, amino groups, alkoxy groups, aromatic ring oxygen groups, aromatic heterocyclooxy groups, amide groups, alkylthio groups, aromatic ring sulfur groups, heteroaromatic ring sulfur groups, silicon groups, boron groups, etc.

[0074] It can be understood that the electrolyte reaction also includes an initiator for initiating the polymerization of the polymerization monomer, and the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, tert-butyl peroxyethyl octanoate, dioctyl peroxydicarbonate, isopropyl hydroperoxide, tert-butyl hydroperoxide, diisopropyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl peroxybutyl valerate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, cyclohexanone peroxide, and methyl ethyl ketone peroxide.

[0075] In a specific embodiment, the curing and formation method of the battery comprises the following steps: subjecting a battery precursor comprising an electrolyte precursor solution to a curing and formation treatment, a curing treatment, and a formation treatment in sequence:

[0076] The curing treatment includes: charging the battery precursor to a voltage of 3.7V at a temperature of 60°C to 80°C, a pressure of ≤5MPa, and a rate of ≤0.3C;

[0077] The curing treatment comprises: curing the battery precursor after the curing treatment at a temperature of 60° C. to 90° C. and a pressure of ≤5 MPa for a time of 2 hours to 8 hours;

[0078] The formation treatment comprises: charging the cured battery precursor to a cut-off voltage of ≥4.0V at a temperature of 60°C to 80°C, a pressure of ≤5MPa, and a rate of ≤0.5C.

[0079] The present application adopts a curing and chemical formation treatment-curing and chemical formation treatment. Specifically, the curing and chemical formation treatment process simultaneously undergoes polymerization curing reaction and chemical formation reaction, which is used to polymerize and cure the polymer monomers to form an electrolyte skeleton on the one hand; on the other hand, the active components in the electrolyte precursor solution can be directional to form a stable interface film on the surface of the positive electrode plate, so that the positive electrode plate has good thermal stability; then heating is performed for sufficient curing to remove unreacted polymer monomers; finally, conventional chemical component sorting treatment is performed to obtain a battery.

[0080] The battery provided in the present application may be a solid-state battery or a semi-solid-state battery, and the electrolyte in the battery may be a solid-state electrolyte or a semi-solid-state electrolyte.

[0081] When the battery is a semi-solid-state battery, the electrolyte further includes a lithium salt and a non-aqueous organic solvent.

[0082] Furthermore, the lithium salt can be selected from the electrolyte lithium salts commonly used in the art, including but not limited to one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide.

[0083] The non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

[0084] Among them, the cyclic carbonate is selected from one or more of ethylene carbonate and propylene carbonate, the linear carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, and the linear carboxylic acid ester is selected from at least one of ethyl propionate, propyl propionate and propyl acetate.

[0085] Furthermore, the mass fraction of cyclic carbonate in the non-aqueous organic solvent is 20-60 wt%, and the mass fraction of linear carbonate and / or linear carboxylate is 40-80 wt%.

[0086] In addition, the electrolyte further includes additives, which include but are not limited to one or more of tris(trimethylsilyl) borate, lithium bis(oxalato) borate, lithium difluoro(oxalato) borate, tetramethyl borate, trimethyl borate, trimethylcyclotriboroxane, tris(2,2,2-trifluoroethyl) phosphite, triphenyl phosphite, tris(trimethylsilyl) phosphite, trimethyl phosphite, triallyl phosphate, 1,3-propane sultone, trifluoromethyl phenyl sulfide, allyloxytrimethylsilane, 1,3,5-trihydroxybenzene, cyclohexylbenzene, ethylene sulfite, ethylene sulfate, propylene sulfite, ethylene carbonate, ethylene ethyl carbonate, propylene sulfate, phenylacetone, 1,4-butane sultone, 1,3-propane sultone, 4-methyl ethylene sulfate, 4-methyl ethylene sulfite, diethyl(cyanomethyl) phosphate, N,N-dimethylformamide, and methylene methanedisulfonate.

[0087] In a specific embodiment, when the battery is a semi-solid battery, the electrolyte includes 0.5 wt% to 9 wt% of polymer and 91 wt% to 99.5 wt% of electrolyte solution.

[0088] The preparation method of the battery provided by this application can be prepared according to the conventional methods in the art.

[0089] In a specific embodiment, first, a positive electrode sheet and a negative electrode sheet are prepared. The preparation method of the positive electrode sheet includes: mixing a positive electrode active material, a binder, a conductive agent, and an additive, adding a solvent (such as N-methylpyrrolidone), and stirring under the action of a vacuum mixer until a positive electrode paste with uniform fluidity is obtained. Then, the positive electrode paste is coated on one or both sides of the positive electrode current collector, air-dried at room temperature, transferred to an oven for drying, and then obtained the positive electrode sheet through cold pressing and slitting.

[0090] In a specific embodiment, the material of the positive electrode sheet provided by this application can be a conventional material in the art. For example, the positive electrode current collector can be a conventional metal foil such as aluminum foil; the positive electrode active material layer includes a positive electrode active material, a conductive agent, a binder, and an additive. Among them, the positive electrode active material can be selected from lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (Li z Ni x Co y Mn 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0 < x + y < 1), lithium manganese oxide (LiMnO2), lithium nickel cobalt aluminum oxide (Liz Ni x Co y Al 1-x-y O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, 0.8 ≤ x + y < 1), lithium nickel cobalt manganese aluminate (Li z Ni x Co y Mn w Al 1-x-y-w O2, where 0.95 ≤ z ≤ 1.05, x > 0, y > 0, w > 0, 0.8 ≤ x + y + w < 1), nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution cathode material (xLi2MnO3·(1 - x)LiMO2, where M = Ni / Co / Mn), lithium nickel cobalt oxide (LiNi x Co y O2, where x > 0, y > 0, x + y = 1), lithium nickel titanium magnesium oxide (LiNi x Ti y Mg z O2, where, x > 0, y > 0, z > 0, x + y + z = 1), lithium nickel oxide (Li2NiO2), spinel lithium manganese oxide (LiMn2O4), nickel cobalt tungsten material, lithium nickel manganese oxide, lithium sodium cobalt oxide (Li n1-y1 Na y1 Co 1- a1-b1 M1 b1 M2 a1 O2 or Li n2-y2-b2 Na y2 Co 1-a2 M1 b2 M2 a2 O2, 0.6 ≤ n1 ≤ 0.8, 0 < y1 ≤ 0.05, 0 ≤ a1 ≤ 0.1, 0 < b1 ≤ 0.1, 0 < b1 / (1 - a1 - b1) < 0.1; 0.6 ≤ n2 ≤ 0.8, 0 < y2 ≤ 0.05, 0 ≤ a2 ≤ 0.1, 0 < b2 ≤ 0.02; M1 is selected from at least one of Te, W, Al, B, P, and K; M2 is a doping element different from M1 such as Mg, Zr, Y, La, Ni, etc.).

[0091] The method for preparing the negative electrode sheet includes: mixing the negative electrode active material, binder, conductive agent, and additive, adding a solvent (such as deionized water), obtaining a negative electrode slurry under the action of a vacuum mixer, then uniformly coating the negative electrode slurry on one or both sides of the negative electrode current collector, drying at room temperature and then transferring it to an oven for drying, and then obtaining the negative electrode sheet through cold pressing and slitting.

[0092] The negative electrode current collector can be selected from negative electrode current collectors commonly used in the art, such as copper foil, etc. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and additives. The negative electrode active material can be selected from silicon, silicon carbon, SiOx (0<X<2), lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerene, graphene, coke, carbon fiber, boron and its derivatives (such as boron powder, boron oxide), aluminum and its derivatives (such as aluminum powder, lithium aluminum alloy), magnesium and its derivatives (such as magnesium, magnesium aluminum alloy), bismuth and its derivatives (such as bismuth, lithium bismuth alloy), nickel and its derivatives (such as nickel, lithium nickel alloy, lithium nickel nitride), silver and its derivatives (such as silver powder, lithium silver alloy), zinc and its derivatives (such as zinc powder, zinc lithium alloy, zinc nitride), titanium and its derivatives (such as titanium powder, lithium titanate, titanium dioxide, lithium titanium alloy, etc.), gallium and its derivatives (such as gallium, lithium gallium alloy), indium and its derivatives (such as indium powder, lithium indium alloy), tin and its derivatives (such as tin powder, stannous oxide, tin oxide, tin sulfate), lithium nitride, and copper nitride. One or more.

[0093] The conductive agent, binder and additives may be selected from the conductive agents, binders and additives conventionally used in the art, and will not be described in detail here.

[0094] The positive electrode sheet, the separator and the negative electrode sheet are stacked and assembled in sequence to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor liquid is added, and the battery is prepared after the processes of packaging, curing and forming treatment, curing treatment and forming treatment.

[0095] The battery provided in this application will be described in detail below with reference to specific embodiments.

[0096] Example 1

[0097] The preparation method of the battery provided in this embodiment is as follows:

[0098] 1) Preparation of positive electrode sheet

[0099] Nickel cobalt manganese (811), polyvinylidene fluoride, and carbon nanotubes are mixed in a weight ratio of 99:0.8:0.2, N-methylpyrrolidone is added, and the mixture is stirred under a vacuum mixer to obtain a positive electrode slurry with a solid content of 68%; the positive electrode slurry is coated on both sides of an aluminum foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain positive electrode sheets.

[0100] 2) Preparation of negative electrode sheet

[0101] The negative electrode active materials graphite and silicon carbon (4:1), polystyrene-butadiene rubber, polyacrylic acid, sodium carboxymethyl cellulose, carbon nanotubes and conductive carbon black are added to deionized water in a weight ratio of 95:1:2:1:0.2:0.8, and stirred under a vacuum mixer to obtain a negative electrode slurry with a solid content of 42%; the negative electrode slurry is coated on both sides of the copper foil, dried at room temperature, and then transferred to an 80°C oven for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0102] 3) Preparation of electrolyte precursor solution

[0103] 0.5% pentaerythritol tetraacrylate, 0.025% benzoyl peroxide, 28% propylene carbonate (PC), 16% ethylene carbonate (EC), 12% diethyl carbonate (DEC), 28% methyl ethyl carbonate (EMC), 13.75% fluoroethylene carbonate (FEC), and 1.725% vinylene carbonate (VC) are uniformly mixed in a mass ratio to obtain a transparent liquid. Lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide (10:1) are added to the transparent liquid and dissolved to obtain an electrolyte precursor solution with a lithium salt concentration of 1.19 mol / L.

[0104] 4) Battery assembly

[0105] The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked and assembled to obtain a battery cell, the battery cell is placed in an outer package, an electrolyte precursor solution is added, and a battery is prepared after packaging, curing and formation treatment, curing, and formation processes;

[0106] The curing treatment includes: charging the battery precursor to a voltage of 3.7V at a temperature of 80°C, a pressure of 5MPa, and a rate of 0.3C; then, curing the battery precursor after the curing treatment at a temperature of 90°C and a pressure of 5MPa for 2 hours; and charging the cured battery precursor to 4.2V at a temperature of 80°C, a pressure of 5MPa, and a rate of 0.5C to obtain a battery.

[0107] The preparation methods of the batteries of Examples 2 to 9 and Comparative Examples 1 to 2 are basically the same as those of Example 1, except that the positive electrode slurry formulation, negative electrode slurry formulation, electrolyte precursor solution composition (excluding lithium salt), and curing conditions are different. The specific differences are listed in Table 1.

[0108] Table 1

[0109] Test example

[0110] 1. Thermogravimetric analysis

[0111] The batteries provided in Examples 1 to 9 and Comparative Examples 1 to 2 were disassembled, and the positive electrode sheets were vacuum treated at 25°C for 36 hours. The positive electrode active material layer was subjected to thermogravimetric analysis. In an oxygen atmosphere, the mass M0 of the positive electrode active material layer was measured at an initial temperature of 25°C. The temperature was then increased at a heating rate of 5°C / min, and the mass M of the positive electrode active material layer was measured at different temperature nodes. n , with temperature as the abscissa and the mass of the positive electrode active material layer as the ordinate, a thermogravimetric curve is drawn. The thermogravimetric curves of the positive electrode active material layer in the batteries provided by Examples 1 to 4 are shown in Figures 2 to 5, and the thermogravimetric data of the positive electrode active material layer in the batteries provided by Examples 1 to 9 and Comparative Examples 1 to 2 are shown in Table 2.

[0112] 2. Furnace temperature test conditions

[0113] The batteries provided in Examples 1 to 9 and Comparative Examples 1 to 2 were discharged at 25°C ± 5°C and 0.2C to the lower limit voltage, allowed to stand for 10 minutes, and then charged at 0.5C to the upper limit voltage, cut off at 0.05C, allowed to stand for 10 minutes, and the voltage of the fully charged battery was tested. The batteries were placed in a thermal shock test chamber and heated to 150°C at a rate of 5°C ± 2°C / min. The batteries were taken out at different times and the battery voltage was tested. The test results are shown in Table 3.

[0114] 3. High temperature intermittent cycle test

[0115] The batteries provided in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to intermittent cycling at 45°C. The batteries were placed at 45°C for 60 minutes, charged at 2.0C to the upper limit voltage, with a cutoff current of 0.05C, placed for 5 hours, and discharged at 2.0C to the lower limit voltage. The capacity retention of the batteries was tested after the corresponding number of cycles. The test results are shown in Table 4.

[0116] Table 2 Note: The sum of the mass retention rate of the positive electrode active material layer at temperature T and the weight loss rate at the current temperature T is 100%.

[0117] Table 3

[0118] Table 4

[0119] According to the data provided in Table 2-4, compared with Comparative Example 1-2, the positive electrode active material layer provided by Example 1-9 has a higher mass loss during the heating process, indicating that there are certain substances in the positive electrode active material layer provided by Example 1-9 that will decompose during the heating process, absorb part of the heat brought by the heating, reduce the effect of temperature on the thermal stability and structural stability of the positive electrode sheet, prevent the battery from voltage decay during the furnace temperature test, improve the high-temperature intermittent cycle performance of the battery, and increase the service life of the battery.

[0120] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A battery, wherein: The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector; In an oxygen atmosphere, a thermogravimetric analysis is performed on the positive electrode active material layer at a heating rate of 5° C. / min. The positive electrode active material layer has at least one weight loss peak between 100° C. and 600° C.

2. The battery according to claim 1, wherein The weight loss rate of the positive electrode active material layer at 100° C. to 600° C. is not higher than 15%.

3. The battery according to claim 1, wherein In an oxygen atmosphere, starting from an initial temperature T0, a thermogravimetric analysis is performed on the positive electrode active material layer at a heating rate of 5°C / min, wherein the initial temperature T0 is 25°C; The positive electrode sheet satisfies at least one of the following: (1) When the temperature T reaches 100°C from T0, the weight loss rate of the positive electrode active material layer is 0.01% to 1.68%; (2) When the temperature T increases from 100°C to 200°C, the weight loss rate of the positive electrode active material layer is 0.05% to 3.64%; (3) When the temperature T increases from 200°C to 300°C, the weight loss rate of the positive electrode active material layer is 0.10% to 6.47%; (4) When the temperature T increases from 300°C to 400°C, the weight loss rate of the positive electrode active material layer is 0.22% to 8.77%; (5) When the temperature T increases from 400°C to 500°C, the weight loss rate of the positive electrode active material layer is 0.66% to 10.47%; (6) When the temperature T increases from 500° C. to 570° C., the weight loss rate of the positive electrode active material layer is 0.93% to 12.66%.

4. The battery according to claim 1, wherein The porosity of the positive electrode plate is 15% to 40%.

5. The battery according to claim 1, wherein The true density of the positive electrode sheet is 3.5 to 4.5 g / cm 3 .

6. The battery according to claim 1, wherein The compaction density of the positive electrode sheet is 2.8 to 4.5 g / cm 3 .

7. The battery according to claim 1, wherein The positive electrode plate includes an electrolyte.

8. The battery according to claim 7, wherein The electrolyte includes a polymer obtained by polymerizing a polymerized monomer, wherein the polymerized monomer includes a functional group, and the functional group includes at least two acrylate groups.

9. The battery according to claim 1, wherein The battery is obtained by sequentially subjecting a battery precursor to a curing treatment, a curing treatment and a formation treatment; The curing treatment includes: charging the battery precursor to a voltage of 3.7V at a temperature of 60°C to 80°C, a pressure of ≤5MPa, and a rate of ≤0.3C; The curing treatment comprises: curing the battery precursor after the curing treatment at a temperature of 60° C. to 90° C. and a pressure of ≤5 MPa, and the treatment time is 2 hours to 8 hours; The formation treatment comprises: charging the battery precursor after the curing treatment to a cut-off voltage of ≥4.0V at a temperature of 60°C to 80°C, a pressure of ≤5MPa, and a rate of ≤0.5C.

10. The battery according to claim 1, wherein The battery comprises an electrolyte, wherein the electrolyte comprises a polymer obtained by polymerizing a polymerized monomer, wherein the polymerized monomer comprises a functional group, and the functional group comprises at least two acrylate groups.

11. The battery according to claim 8 or 10, wherein: The polymerizable monomer is selected from one or more of a difunctional monomer, a trifunctional monomer, a tetrafunctional monomer, and a hexafunctional monomer; The bifunctional monomer is selected from one or more of dipropylene glycol diacrylate and its derivatives, polyethylene glycol diacrylate and its derivatives, tripropylene glycol diacrylate and its derivatives, 1,6-hexanediol diacrylate and its derivatives, ethylene glycol dimethacrylate and its derivatives, ethoxylated bisphenol A diacrylate and its derivatives, diethylene glycol dimethacrylate and its derivatives, triethylene glycol dimethacrylate and its derivatives, neopentyl glycol diacrylate and its derivatives, and 1,5-pentanediol diacrylate and its derivatives; And / or, the trifunctional monomer is selected from one or more of ethoxylated trimethylolpropane triacrylate and its derivatives, pentaerythritol triacrylate and its derivatives, trimethylolpropane triacrylate and its derivatives, trimethylolpropane trimethacrylate and its derivatives, pentaerythritol triacrylate and its derivatives; and / or, the tetrafunctional monomer is ethoxylated (5) pentaerythritol tetraacrylate and its derivatives; And / or, the hexafunctional monomer is dipentaerythritol hexaacrylate and its derivatives.

12. The battery according to claim 10, wherein The electrolyte also includes a lithium salt and a non-aqueous organic solvent.

13. The battery according to claim 12, wherein: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium bisfluorooxalatoborate, lithium bisfluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, lithium difluorophosphate, lithium perchlorate, lithium bisfluorosulfonamide and lithium bistrifluoromethylsulfonyl imide; And / or, the non-aqueous organic solvent is selected from one or more of cyclic carbonates, linear carbonates, and linear carboxylates.

14. The battery according to claim 10, wherein The electrolyte also includes an additive, which includes one or more of tris(trimethylsilyl)borate, lithium bis(oxalatoborate), lithium bis(fluorooxalatoborate), tetramethyl borate, trimethyl borate, trimethylcyclotriboroxane, tris(2,2,2-trifluoroethyl)phosphite, triphenylphosphite, tris(trimethylsilyl)phosphite, trimethylphosphite, triallyl phosphate, 1,3-propane sultone, trifluoromethylphenyl sulfide, allyloxytrimethylsilyl, 1,3,5-hydroxybenzene, cyclohexylbenzene, ethylene sulfite, ethylene sulfate, propylene sulfite, ethylene carbonate, ethylene ethylene carbonate, propylene sulfate, phenylacetone, 1,4-butane sultone, 1,3-propane sultone, 4-methylethylene sulfate, 4-methylethylene sulfite, diethyl(cyanomethyl)phosphate, N,N-dimethylamide, and methylene methanedisulfonate.

15. The battery according to any one of claims 1 to 14, wherein: The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, nickel cobalt aluminum tungsten material, lithium-rich manganese-based solid solution positive electrode material, lithium nickel cobalt oxide, lithium nickel titanium magnesium oxide, lithium nickel oxide, spinel lithium manganese oxide, nickel cobalt tungsten, lithium nickel manganese oxide, and sodium-containing lithium cobalt oxide.

16. The battery according to claim 1, wherein The battery is a solid-state battery or a semi-solid-state battery.

17. The battery according to claim 7 or 10, wherein: The electrolyte is a semi-solid electrolyte or a solid electrolyte.

18. The battery according to claim 1, wherein It also includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes one or more of silicon, silicon carbon, SiOx, lithium silicon alloy, silicon alloy, artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, fullerenes, graphene, coke, carbon fiber, boron and its derivatives, aluminum and its derivatives, magnesium and its derivatives, bismuth and its derivatives, nickel and its derivatives, silver and its derivatives, zinc and its derivatives, titanium and its derivatives, gallium and its derivatives, indium and its derivatives, tin and its derivatives, lithium nitride, and copper nitride.

19. An electronic device, wherein: A battery comprising any one of claims 1 to 18.

Citation Information

Cited By

  • Battery monomer, battery device, power utilization device and energy storage device

    CN120089800A